How relevant is microeconomic analysis to climate change and healthcare? - Ramesh, Sangaralingam (Henry Stewart Talks, 2019)
Healthcare costs, Market failure, Emissions trading system, Climate change, Welfare economics, Perfect competition, Material cost, Opportunity cost